Exploring the challenges and implications of atheism for religious society in Malaysia - Ahmad Faizuddin Ramli,; Aemy Elyani Mat Zain,; Ammar Badruddin Romli,; Rehman, Ata Ur; Ahmad Moghr, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Atheism is an ideology that rejects the existence of God and has gained increasing prominence in societies globally, including Malaysia. Atheism significantly challenges the religious orientation of Malaysian society. Specifically, atheism challenges spiritual and ethical foundations, unity, and cultural heritage linked to religious beliefs. Understanding these challenges is vital to formulate proactive measures, education, and informed dialogue to mitigate the negative impact of atheism on Malaysian society. This study explored the effects of atheism on Malaysian religious society via library research analysis. Scholarly articles, books, and reputable online resources on religious and atheism underwent content analysis, which yielded five key findings. Firstly, atheism leads to the loss of spiritual guidance and morality. Secondly, atheism potentially erodes ethical values and societal norms, and subsequently reduces social trust and cohesion. Thirdly, atheism contributes to moral relativism and ethical ambiguity, which potentially undermines established moral frameworks and social norms. Fourthly, atheism can weaken community cohesion. Lastly, ‎atheism threatens religious institutions and practices. Additionally, the absence of the role of God might undermine the cultural and heritage importance of religion. This study presented critical insights on the negative societal effects of atheism. By exploring the potential consequences of atheism on social cohesion, moral foundations, and existential perspectives, this study highlighted the need for religious education as part of atheism prevention and rehabilitation.